2022
DOI: 10.31234/osf.io/tgf27
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing human habits in the lab

Abstract: Habits pose a fundamental puzzle for those aiming to understand human behavior. They pervade our everyday lives and dominate some forms of psychopathology but are extremely hard to elicit in the lab. In this Registered Report, we develop novel experimental paradigms grounded in computational models, which suggest that habit strength should be proportional to the frequency of behavior and, in contrast to previous research, independent of value. Specifically, we manipulate how often participants perform response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…It is related to stimulus-response (S-R) learning, as repetition facilitates the formation of S-R associations and re-cency effects in value-based decision-making tasks ( Guthrie, 1952; Wood and Rünger, 2016; Watson et al, 2022 ). The repetition bias is also consistent with previous proposals for the role of action repetition in the development of habitual behavior ( Thorndike, 1911; Miller et al, 2019; Schwöbel et al, 2021; Nebe et al, 2024 ). Similarly, behavioral repetition of action sequences has been identified as a way to optimize the trade-off between maximizing reward and a reduction of policy complexity ( Gershman, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is related to stimulus-response (S-R) learning, as repetition facilitates the formation of S-R associations and re-cency effects in value-based decision-making tasks ( Guthrie, 1952; Wood and Rünger, 2016; Watson et al, 2022 ). The repetition bias is also consistent with previous proposals for the role of action repetition in the development of habitual behavior ( Thorndike, 1911; Miller et al, 2019; Schwöbel et al, 2021; Nebe et al, 2024 ). Similarly, behavioral repetition of action sequences has been identified as a way to optimize the trade-off between maximizing reward and a reduction of policy complexity ( Gershman, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the repetition learning mechanism is different from stimulus-response associa- The repetition bias is possibly a prerequisite for the development of habitual behavior (Wood and Rünger, 2016;Miller et al, 2019;Schwöbel et al, 2021;Nebe et al, 2024). This opens up possibilities to use this mechanism and its predictions to investigate the formation of habits.…”
Section: Relation To Other Models and Implications For Habit Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…A prediction of our findings is that anhedonia may not only manifest as a deficit in perseveration, but may also manifest as a deficit in habit formation. Intriguingly, recent work on the origin of habits has revealed that they are largely divorced from reward [44]. If true, this would highlight a cognitive deficit in anhedonia unrelated to reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings demonstrate regularities in smartphone user behaviors that can be interpreted as habitual, the behavioral science literature has taken a different approach, often relying on relatively simple behavioral measures (e.g., behavioral frequency, reward devaluation [35,36]) or self-report measures to assess habits (e.g., Self-Report Habit Index [37], Self-Report Behavioral Automaticity Index [38], Unified Theory of Acceptance and Use of Technology questionnaire [39], Response Frequency Measure of Media Habit [40]). These methods have proven useful in past research, but they are also limited in at least two important ways.…”
Section: Introductionmentioning
confidence: 98%